Herman Hertzberger - Herzberger, Herman; McCarter, Robert, 1955- (2015)
Herman Hertzberger is one of the most important and critically influential figures in international architecture of the last 50 years. He has consistently championed a fundamentally humanist modern architecture, rooted in its place and history, while simultaneously opening up new possibilities for dwelling. In this monograph, Robert McCarter examines Hertzberger's most important architectural works through analysis of the design process and guiding ideas, particularly as these reflect Hertzberger's engagement with the Modernist tradition, architectural history, urban space and the way we experience it -- page 4 of cover.
Beginnings: towards an architecture shaped by the life that takes place within it -- Housing -- Schools -- Workplaces -- Cultural buildings -- Urban designs -- Space and the life-world: lessons from the experience of architecture.
Includes bibliographical references.
Keywords: Hertzberger, Herman -- Catalogs; Architecture, Dutch -- History -- 20th century -- Catalogs; Architecture, Dutch -- History -- 21st century -- Catalogs